Analisis Bauran Pemasaran untuk Meningkatkan Penjualan (Studi Kasus Pada Toko Astina di Desa Kendalrejo, Kec. Durenan, Kab. Trenggalek) - Purnamasari, Diah Sasti; Suryaningsih, Tutut (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
The purpose of this study is to determine the marketing mix used in the Astina Store and the role of HR and the use of technology in the Astina Store which is used as a strategy to increase sales. So that Toko Astina can survive during the Covid-19 pandemic and from the many competitors with similar businesses in the area. The method in this study is qualitative research with a descriptive approach. The results of this study indicate that of the four marketing mixes that have been used as a strategy to increase sales, they have been used properly. However, there are still some marketing mixes that have not been used optimally, such as promotion, human resources, and the use of technology which has not been used optimally so that business owners can still develop new strategies by combining the strategies that have been used with new strategies that are by the times so that the right and effective combination can be obtained to increase sales at the Astina Store.